2015
DOI: 10.1183/16000617.00000315
|View full text |Cite
|
Sign up to set email alerts
|

An official American Thoracic Society/European Respiratory Society statement: research questions in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity, mortality and resource use worldwide. The goal of this official American Thoracic Society (ATS)/European Respiratory Society (ERS) Research Statement is to describe evidence related to diagnosis, assessment, and management; identify gaps in knowledge; and make recommendations for future research. It is not intended to provide clinical practice recommendations on COPD diagnosis and management.Clinicians, researchers and patient advoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 126 publications
(123 reference statements)
0
60
0
1
Order By: Relevance
“…4 A recent task-force document emphasized the need for additional research involving smokers with symptoms and normal lung function. 5 …”
mentioning
confidence: 99%
“…4 A recent task-force document emphasized the need for additional research involving smokers with symptoms and normal lung function. 5 …”
mentioning
confidence: 99%
“…We decide to present both AL GOLD and L LLN as a joint American Thoracic Society/European Respiratory Society (ATS/ERS) statement called for investigations of comparisons between the fixed cut-off (FEV 1 /FVC < 0.7) and the LLN-based definition (FEV 1 /FVC < LLN) of airflow limitation in predicting adverse health outcomes (Celli et al 2015). Our results also indicated that both definitions predicted an adverse outcome.…”
Section: Discussionmentioning
confidence: 76%
“…We also assessed the effects of repeat PRP not only on exercise capacity changes, but also on quality of life and mood, as the importance of patient-centered outcomes in COPD is being increasingly recognized 27. We used mixed-effects modeling, which is the ideal approach for analysis of multiple repeated measurements in each patient, factoring in time between PRPs as a random effect 28.…”
Section: Discussionmentioning
confidence: 99%